Interdisciplinarity and statistics in the data of slaves buried at Porto Alegre (1850 to 1885) - Mello, Leila Inês de; Dalcin, Andreia; Nunes, Luciana Neves (Universidade Estadual de Campinas, 2020)
This paper presents results of a research of a professional master in the field of Statistical Education done with 7th grade students in a private school in Canoas-RS. The question “Can the search for understanding demographic data of slaves buried in the cemetery of the Santa Casa de Porto Alegre, in the XIX Century, contribute to the learning of statistics?” served for an interdisciplinary project in Mathematics, History and Science. With a random sample of 1559 slave death records from the book “Africanos na Santa Casa de Porto Alegre: Óbitos dos escravos sepultados no cemitério da Santa Casa (1850 a 1885)” the class produced charts and tables. Through pretest and posttest it was evaluated that there were advances in the learning of statistical concepts. The statistical concepts were mobilized in the activities and the interdisciplinary look favored the process of data production and analysis, as well as assisted in the debate about black slavery in Porto Alegre in the XIX Century.